Effect of Stabilizer and Moringa Leaves Concentration on the Dragon Fruit Velva: Pengaruh Jenis Bahan Penstabil dan Daun Kelor (Moringa oleifera) Dalam Pembuatan Velva Buah Naga Merah (Hylocereus polyrhizus) - Adelia Putri Sari Yahya Adel; Merkuria Karyantina; Nanik Suhartatik (Agrobiotek, 2024)
Velva, a kind of frozen dessert, made from fruit that contains nutrients and help the body's metabolic processes as a source of energy. Red dragon fruit (Hylocereus polyrhizus) is used in the production of velva in order to get a good color and Moringa to increase antioxidant activity. The purpose of this study was to determine the appropriate substitution ratio between velva, dragon fruit, moringa leaf extract, and stabilizer to produce dragon fruit velva with good characteristics, namely high antioxidant and preferred by consumers. This study used a factorial completely randomized design (CRD). The factors used were the concentration of Moringa leaves (8, 10, 12 g) and the concentration of the type of stabilizer (CMC 1,26%, cornstarch 1,26%, carrageenan 1,26%). The best chemical analysis was treatment concentration of carrageenan stabilizer 1,26% with the addition of 8 g Moringa leaf extract with antioxidant activity 16,85%, crude fiber 0.63%, vitamin C 4,33%, reducing sugar 11,83%, total phenolic 13,93mg.GAE/ml and pH 3,5. Physical analysis with melting power 47.00 minutes/hour, overrun 13,00%, TPT 4˚Brix and TAT 1.14%. The results of the red dragon fruit velva sensory test with various types of stabilizers and the addition of Moringa leaves, as well as the combination of treatments between the two had no significant effect on color, texture, taste, aroma and overall preference. The best organoleptic analysis was the P3K1 treatment (concentration of carrageenan stabilizer 1,26% with the addition of 8 g Moringa leaf extract) with a color value of 3.06, taste 2.57, aroma 2.78, texture 3.50 and overall preference 3,42.